2019
DOI: 10.1590/0102-311x00223018
|View full text |Cite
|
Sign up to set email alerts
|

Avanços na assistência ao parto no Brasil: resultados preliminares de dois estudos avaliativos

Abstract: Resumo: Este artigo tem como objetivo descrever os primeiros resultados de dois estudos avaliativos, um sobre a Rede Cegonha e outro sobre o projeto Parto Adequado, denominados, respectivamente, de avaliação da Rede Cegonha e Nascer Saudável, e identificar possíveis melhorias em comparação ao estudo Nascer no Brasil. Ambos os estudos têm desenho seccional, realizados em 2017. O estudo avaliação da Rede Cegonha incluiu todas as 606 maternidades públicas e mistas envolvidas na Rede Cegonha e um total de 10.675 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
1
82

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(141 citation statements)
references
References 41 publications
5
53
1
82
Order By: Relevance
“…Among the practices in use in health services, they mentioned the presence of companion, nonpharmacological methods of pain relief, breastfeeding in the first hour of life, skin-to-skin contact, timely cord clamping, and freedom of movement position, among other possibilities. This finding was consistent with the results of Côrtes et al [26] According to Leal, [27] the presence of nursing in childbirth care is associated with better results in obstetric clinical practice, with the use of non-pharmacological pain relief methods, reduction of unnecessary interventions, women's satisfaction with the care received and positive perinatal outcomes.…”
Section: Search For the Alignment Between Theory And Practicesupporting
confidence: 91%
See 1 more Smart Citation
“…Among the practices in use in health services, they mentioned the presence of companion, nonpharmacological methods of pain relief, breastfeeding in the first hour of life, skin-to-skin contact, timely cord clamping, and freedom of movement position, among other possibilities. This finding was consistent with the results of Côrtes et al [26] According to Leal, [27] the presence of nursing in childbirth care is associated with better results in obstetric clinical practice, with the use of non-pharmacological pain relief methods, reduction of unnecessary interventions, women's satisfaction with the care received and positive perinatal outcomes.…”
Section: Search For the Alignment Between Theory And Practicesupporting
confidence: 91%
“…More than 50% of the respondents reported that they did were not aware of the existence of written norms guiding the practices of attention to natural childbirth, which corroborates the lack of definition in the team's work processes. For Leal, [27] the low implementation of clinical protocols is reported worldwide and may be associated with the characteristics of the clinical protocol itself, the healthcare professional, the patient, the external environment, among other causes.…”
Section: Nonexistence Of a Unit Protocolmentioning
confidence: 99%
“…According to a national study carried out with survey data from the Rede Cegonha evaluation, the proportion of episiotomy was 27.7% in public hospitals. However, data were self-reported by the parturient (9) . This procedure is performed in the Brazilian scenario in 27.7% of women in public institutions and 39.4% in the private sector (9) .…”
Section: Introductionmentioning
confidence: 99%
“…However, data were self-reported by the parturient (9) . This procedure is performed in the Brazilian scenario in 27.7% of women in public institutions and 39.4% in the private sector (9) .…”
Section: Introductionmentioning
confidence: 99%
“…8 Although technological innovations have undeniable contributions, such as reduction of maternal and neonatal mortality, indication of cesarean childbirth in the face of obstetric and fetal emergencies, inappropriate use of technologies and unnecessary interventions without scientific evidence during childbirth, they are substantiated as iatrogenic behaviors that can harm the health of mothers and children. 9 Therefore, it is questioned the routine use of such procedures and, mainly, exploration/colonization of the female body as an object of intervention, without being allowed to experience childbirth according to their needs or enabling conditions of access to other forms of knowledge that provide qualification and humanization of care.…”
Section: Decolonization Of Knowledge: Performance Of Nurse-midwives Imentioning
confidence: 99%